Literatur Review: Pengaruh Pemberian Supplement Folamil dan Tablet Zat Besi pada Ibu Hamil dengan Anemia terhadap Peningkatan Kadar Hemoglobin - Honaryati Honaryati; Nilawati Usman; Mardiana Ahmad (Faletehan Health Journal, 2021)
Anemia in pregnancy is a deficiency of iron that plays a role in the formation of hemoglobin, namely protein, iron, vitamin B12, vitamin C and folic acid. Folic acid plays a role in the metabolism of amino acids necessary in the formation of red blood cells to prevent from the occurrence of birth defects and anemia. This was a descriptive literature study. The articles search used Mendeley app with the year of publication from 2017 to 2021 and obtained 10 articles that are relavant with inclusion criteria. According to the 10 articles that are eligiable and meet the determined criteria, the provision of folamil supplement and iron tablets to pregnant women with anemia had a significant effect on the increase of hemoglobin level. During pregnancy, the pregnant women got poor nutrients intake and had insufficient supplies of iron and folic acid. Health workers especially midwives should increase the scope of folamil supplement and iron tablets administration by improving the role of community and pregnant women in order to increase the use of health facility.